Cover Image, Volume 8, Issue 2. (March 2016) - Tong, Xin; Feng, Yang; Zhao, Anqi
Abstract : The cover image, by Xin Tong et al., is based on the Advanced Review A Survey on Neyman‐Pearson Classification and Suggestions for Future Research, DOI:10.1002/wics.1376 . Abstract : The cover image, by Xin Tong et al., is based on the Advanced Review A Survey on Neyman‐Pearson Classification and Suggestions for Future Research, DOI:10.1002/wics.1376 .